2020
DOI: 10.3389/fimmu.2020.594775
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell-Secreted ISG15 Promotes Tumor Cell Migration and Immune Suppression by Inducing the Macrophage M2-Like Phenotype

Abstract: Interferon-stimulated gene 15 (ISG15) is known to be involved in tumor progression. We previously reported that ISG15 expressed on nasopharyngeal carcinoma (NPC) cells and related to poor prognosis of patients with NPC. We further observed that ISG15 can be secreted by NPC cell and expressed on the macrophages in situ. However, the role of ISG15 in tumor-associated macrophages (TAMs) remains poorly understood. In the present study, we found that ISG15 treatment induces macrophages with M2-like phenotype, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 33 publications
0
40
0
1
Order By: Relevance
“…Although ISG15 protein has been reported to serve as an effective adjuvant to vaccination, 68 it is also known to represent a biomarker of poor prognosis in the cancer setting 69 and to mediate pro-tumor immunoregulatory activity. 70 GSEA supported enhanced vascular-immune crosstalk, innate and adaptive immune cell presence, and antigen-presenting cell function in the TME of patients with IR/PR versus NIR/PD on trial ( online supplemental figure S11 ).…”
Section: Discussionmentioning
confidence: 91%
“…Although ISG15 protein has been reported to serve as an effective adjuvant to vaccination, 68 it is also known to represent a biomarker of poor prognosis in the cancer setting 69 and to mediate pro-tumor immunoregulatory activity. 70 GSEA supported enhanced vascular-immune crosstalk, innate and adaptive immune cell presence, and antigen-presenting cell function in the TME of patients with IR/PR versus NIR/PD on trial ( online supplemental figure S11 ).…”
Section: Discussionmentioning
confidence: 91%
“…Monocytes from blood differentiate to M1 or M2 subtype macrophages, depending on their interactions with other cells present in tissues (Figures 6 and 7). Such differentiation is dependent on the environmental stimuli these cells are subject to (183)(184)(185)(186)(187)(188)(189)(190). The first type of antimicrobial macrophage activation became known as M1 macrophages (191).…”
Section: Polarization Of Macrophagesmentioning
confidence: 99%
“…Meanwhile, ISG15 has been identified as a novel diagnostic biomarker of thyroid papillary microcarcinoma with lymphatic metastasis through proteomic analysis [ 28 ]. Further analysis has found that ISG15 could be secreted by nasopharyngeal carcinoma cells and induced macrophages to M2 polarization, thereby inhibiting the antitumor activity of T cells and accelerating tumor progression, indicating that ISG15 is an important molecule in tumor microenvironment [ 29 ]. However, ISG15 plays a role not only in promoting tumor progression but also in preventing tumor development.…”
Section: Discussionmentioning
confidence: 99%